Предмет: Математика,
автор: mariko109
1. (4b²-3b)*(-3b)
2. (2by+b²)-(by+b²)
3. (-5b+1)*(2b+3)
4.(4b²+3)*(4b²-3)
5.y(3y+1)=3y*(y-2)
Ответы
Автор ответа:
0
(4b^2-3b)(-3b)=-12b^3+9b^2
(2by+b^2)-(by+b^2)=2by+b^2-by-b^2=2by-by
(-5b+1)(2b+3)=-10b^2+2b-15b+3=-10b^2-13b+3
(4b^2+3)(4b^2-3)=16b^4+12b^2-12b^2-9=16b^4-9
y(3y+1)=3y(y-2)
3y^2+y-3y^2+6y=7y
(2by+b^2)-(by+b^2)=2by+b^2-by-b^2=2by-by
(-5b+1)(2b+3)=-10b^2+2b-15b+3=-10b^2-13b+3
(4b^2+3)(4b^2-3)=16b^4+12b^2-12b^2-9=16b^4-9
y(3y+1)=3y(y-2)
3y^2+y-3y^2+6y=7y
Похожие вопросы
Предмет: Математика,
автор: fedor2531
Предмет: Математика,
автор: nataxa71
Предмет: Английский язык,
автор: Joftg
Предмет: Алгебра,
автор: IIPollyII
Предмет: Математика,
автор: asema000